Understanding the conduction mechanism of acceptor-doped ceria oxygen ion conductors by photoluminescence analysis. Issue 19 (1st October 2022) - Wang, Huan; Ma, Yuxin; Yang, Wen; Wang, Dejun; Wang, Chunliang; Yan, Duanting; Liu, Runru
Abstract: Doping or co-doping is a universal and extremely effective strategy for enhancing ion conductivity by modulating the coordination surroundings of oxygen vacancies in oxygen ion conductors. Herein, the structural origin and conduction mechanism of bulk conduction upon cation doping, exemplified in Ce0.85 Sm0.15-x Lax O2-δ (x = 0, 0.03, 0.06, 0.09, 0.12, and 0.15) polycrystalline oxygen ion conductors, were investigated by employing the structure-sensitive photoluminescence properties of Sm 3+ ions. Photoluminescence results show that the oxygen vacancies, introduced by La 3+ substitutions, moved from near the coordination positions of La 3+ ions to those of Sm 3+ and Ce 4+ ions. This occurred when the Sm 3+ ions were substituted by La 3+ ions. Compared with Samarium doped Ceria (SDC), the oxygen vacancies in Lanthanum-doped ceria (LDC) are more likely to be located around the Ce 4+ ions rather than around the trivalent doping cations. For acceptor-doped CeO2 -based oxygen ion conductors, the key factor in the activation energy of bulk conduction, E α b u l k, is the cation electronegativity on the oxygen vacancy migration path rather than the defect association and local lattice distortion on the oxygen vacancy migration path in the lattice. The significance of cation electronegativity to ion conduction proposed in this study would be beneficial for understanding the conduction mechanism and for optimising the electrical properties of various ion conductors. In addition, the strategy developed in this study to shed light on the relationship between cation doping and local structures by photoluminescence could be extended to other ion conductors in solid oxide fuel cells, oxygen sensors, oxygen concentration cells, and memristors.